Switching damping for a frequency-tunable electromagnetic energy harvester - Ooi, B.L. (Elsevier, 2015)
This paper demonstrates the possibility to widen the operational bandwidth of an electromagnetic energy harvester by switching the values of electrical damping coefficient at different points within the oscillating cycle. In this system, the damping in the system is electronically switched by adjusting the value of load resistance used. An analytical model of the switching damping device is presented in which it is shown that altering the damping can increase or decrease the duration of particular segment of the oscillation cycle and so, by selecting appropriate damping, the resonant frequency can be altered. The predictive results are then validated by series of experimental results for the proposed range of resistive load resistances. For the prototype considered, a frequency shift of +1 to -1.3 of the resonant frequency are achieved. However, this shifting of the resonant frequency does come with some loss of average output power, since this is highly susceptible to the electrical induced damping applied to the device. Â© 2015 Elsevier B.V. All rights reserved.